Neuroimmune Interactions in Schizophrenia: Focus on Vagus Nerve Stimulation and Activation of the Alpha-7 Nicotinic Acetylcholine Receptor - Corsi-Zuelli, Fabiana Maria das Graças; Brognara, Fernanda; Quirino, Gustavo Fernando da Silva; Hiroki, Carlos Hiroji; Fais, Rafael Sobrano; Del-Ben, Cristina Marta; Ulloa, Luis; Salgado, Helio Cesar; Kanashiro, Alexandre; Loureiro, Camila Marcelino (Frontiers in Immunology, 2017)
Schizophrenia is one of the most debilitating mental disorders and is aggravated by the lack of efficacious treatment. Although its etiology is unclear, epidemiological studies indicate that infection and inflammation during development induces behavioral, morphological, neurochemical, and cognitive impairments, increasing the risk of developing schizophrenia. The inflammatory hypothesis of schizophrenia is also supported by clinical studies demonstrating systemic inflammation and microglia activation in schizophrenic patients. Although elucidating the mechanism that induces this inflammatory profile remains a challenge, mounting evidence suggests that neuroimmune interactions may provide therapeutic advantages to control inflammation and hence schizophrenia. Recent studies have indicated that vagus nerve stimulation controls both peripheral and central inflammation via alpha-7 nicotinic acetylcholine receptor (α7nAChR). Other findings have indicated that vagal stimulation and α7nAChR-agonists can provide therapeutic advantages for neuropsychiatric disorders, such as depression and epilepsy. This review analyzes the latest results regarding: (I) the immune-to-brain pathogenesis of schizophrenia; (II) the regulation of inflammation by the autonomic nervous system in psychiatric disorders; and (III) the role of the vagus nerve and α7nAChR in schizophrenia.